Integration of Leadership, Motivation, and Culture to Strengthen Organizational Commitment - Sahrif, Ahmad Darul; Imron, Much (Lembaga Penelitian Universitas YARSI, 2025)
This research examines the influence of transformational leadership, work motivation, and organizational culture on organizational commitment at PT Wasa Mitra Engineering, involving all 58 employees through a saturated census sampling technique. The study addresses issues such as a lack of supervisory firmness, leading to frequent employee tardiness. A research gap exists in understanding the mechanism through which these variables affect organizational commitment within the context of PT Wasa Mitra Engineering's power plant industry. To address this gap, the study incorporates employee feedback, including monthly reviews to help employees identify and improve their performance. Work motivation emerges as a key factor in fostering a committed and productive environment, supported by an organizational culture emphasizing honesty, integrity, collaboration, and respect. The findings reveal that transformational leadership does not significantly influence organizational commitment. However, work motivation and organizational culture have a positive effect, highlighting the importance of these factors in shaping employee commitment. This research contributes to the understanding of organizational dynamics, offering practical insights for creating a dedicated workforce. These results also provide a foundation for further studies in related fields, emphasizing the interplay between motivation, culture, and commitment in organizational success.